The Relationship Between School Principals' Managerial Skills and Teacher Performance Quality - Undiadi Undiadi; Muhammad Muhammad (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2025)
The quality of teachers' performance is a key factor in the success of education. This study is significant as it highlights the role of school principals as leaders who can motivate, guide, and support teachers in achieving educational goals. The research aims to analyze the relationship between school principals' managerial skills and the quality of teachers' performance. This study employs a qualitative research method with a case study approach. Data were collected through in-depth interviews, participatory observations, and document analysis at three selected schools. Data analysis was conducted thematically through the stages of data reduction, data presentation, and conclusion drawing to identify the relationship between school principals' managerial skills and the quality of teachers' performance. The results reveal that school principals with strong managerial skills can create a conducive work environment, motivate teachers, and provide support for professional development. This directly impacts the improvement of teachers' performance quality, particularly in lesson planning, implementation, and evaluation. This study concludes that training in managerial skills is crucial for school principals as a strategic effort to enhance the quality of education. The practical implication is the necessity of policies that support the continuous development of school principals' managerial capacities.